1993
DOI: 10.1007/bf00683194
|View full text |Cite
|
Sign up to set email alerts
|

1,25(OH)2D3 modulation of mammary tumor cell growth in vitro and in vivo

Abstract: The biological role of 1,25(OH)2D3 in controlling Ca++ homeostasis in the body has been identified and widely investigated for a long time. More recently its effect in regulating cell proliferation or differentiated activity was described in a variety of normal and malignant cells. The present study was carried out to investigate the different aspects and biological mechanisms of this activity and to determine if the use of 1,25(OH)2D3 in the treatment of breast cancer patients could be considered. It is found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
20
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…Numerous in vitro studies have indicated that 1,25(OH) 2 D can inhibit cell proliferation and promote cell differentiation in breast tumor tissue (5,(9)(10)(11), suggesting that high levels of vitamin D metabolites may be protective against breast cancer. In addition, several ecologic studies have reported lower breast cancer incidence and mortality rates in populations with high sunlight exposure, and thus higher vitamin D levels, compared with those with lower ambient sunlight (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous in vitro studies have indicated that 1,25(OH) 2 D can inhibit cell proliferation and promote cell differentiation in breast tumor tissue (5,(9)(10)(11), suggesting that high levels of vitamin D metabolites may be protective against breast cancer. In addition, several ecologic studies have reported lower breast cancer incidence and mortality rates in populations with high sunlight exposure, and thus higher vitamin D levels, compared with those with lower ambient sunlight (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…These observations, together with experimental evidence showing anticarcinogenic properties of vitamin D, have led to the hypothesis that high levels of vitamin D might reduce the risk of breast cancer (8)(9)(10)(11). In the United States, the main sources of dietary vitamin D intake are vitamin D -fortified dairy products, which are also rich sources of dietary calcium.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Most of the epidemiologic studies regarding breast cancer risk have assessed the effects of vitamin D only for dietary intake yielding inconsistent results. [7][8][9][10][11][12][13][14][15] However, beside dietary intake, the main source of vitamin D is cutaneous production via sun exposure.…”
mentioning
confidence: 99%